Development and improvement of sorghum-based gluten-free dinner rolls - Bianchi, Marc Pierre (Kansas State University, 2013)
Despite the expansion of the gluten-free (GF) food market, some GF food items are still characterized by an overall mediocre quality. The effects of different types of egg ingredients (fresh, whites, dried) and carob germ flour (CGF) as well as par-baking technology on the quality of dough-based gluten-free sorghum dinner rolls were evaluated. Gluten-free rolls containing 30% of fresh shell eggs or equivalent of egg products and 10% of CGF on a flour basis were evaluated against a control (no egg, no CGF). The feasibility of partial baking of rolls was studied on control as well as fresh eggs and carob germ flour formulas during 5 baking times (0, 8, 10, 12 and 18 minutes). Breads were evaluated for crumb and crust color, specific volume, cell profile, Texture Profile Analysis (TPA) and consumer acceptability. Results showed that rolls containing egg ingredients had higher specific volumes than control (p<0.05) with an increase from 1.45 cm[superscript]3/g to 1.96 cm[superscript]3/g. Carob germ flour did not have a significant effect on specific volume. Eggs also improved cell elongation and produced significantly darker crust (p<0.05). CGF did not appear to have an effect on cell elongation but increased average cell number when combined with egg ingredients, and greatly impacted rolls texture. The combination of fresh eggs or egg whites with CGF reduced significantly (p<0.05) crumb hardness from 2,074 to 1,404g and 1,468g of force respectively. Par-baked dinner rolls displayed similar color, volume, cell profile and texture trends to conventionally baked rolls. Sensory study revealed that acceptability, organoleptic characteristics and willingness to buy of par-baked dinner rolls could be similar to that of conventional wheat products. This research proved that the addition of eggs and CGF to a GF rolls formulation resulted in better overall quality of the product. Moreover, par-baking of the rolls showed great potential to provide safe, convenient and acceptable GF foods to celiac individuals.
Keywords: Gluten-free; Eggs; Partial baking; Carob germ flour; Dinner rolls; Food Science (0359)